Strategi Komunikasi Penyuluh Agama Islam Kota Ternate Dalam Mensosialisasikan Moderasi Beragama - Pattilauw, Sawia Tjindrawati (Peneliti.net, 2024)
Ternate society has plural and multicultural characteristics. Due to its multicultural nature, Ternate people are generally open and accept the diversity of views from various factors, including ethnicity, religion, race, and culture, including variations in religious sects. The purpose of this study is to explain about Islamic religious instructors as agents of religious moderation in developing communication strategies consisting of: audience recognition, message preparation, message delivery, and media use. The research method used is a literature study with a qualitative approach. The data analysis technique uses the Miles and Huberman model which consists of data reduction, data presentation and conclusion drawing. The result of this study is that this research highlights the importance of effective communication strategies for Ternate City Islamic Religious Counselors in the Bacarita programme. Kampong Moderasi Beragama. This strategy includes audience recognition, message preparation, message delivery, and selection of appropriate communication media. Audience recognition involves understanding the physical conditions, groups, and situations of the audience, with special attention to the characteristics of the local community. Message preparation is done by taking into account the AIDA formula (attention, interest, desire, and action) using informative, educative, and persuasive methods. Message delivery was done through direct interaction with community leaders and local Islamic organisations. The selection of communication media considers the audience and programme objectives, with the choice of media considered effective being Instagram and YouTube.